(untitled) (Applied Biological Research, 2014)
A field experiment was conducted during rabi seasons of 2009-10, 2010-11 and 2011-12 to assess the effect of 3 tillage practices (conventional tillage, no tillage and rotavator tillage) and 4 sowing methods (conventional sowing, seed-cum-fertilizer drill sowing, paired row sowing and criss-cross sowing) on groundnut production. Tillage methods showed no significant difference in pod yield with maximum yield in rotavator tillage treatment (1570 kg ha-1). Amongst the sowing methods, paired row sowing gave significantly highest pod yield and net returns (1781 kg ha-1and 19730 ha-1, respectively). The interactionbetween tillage practices and sowing methods was non-significant. The study revealed that none of tillage practice effectively enhanced yield, however paired row sowing proved superior in pod yield with 15.6, 22.2 and 25.4% increase over seed-cum-fertilizer drill, criss-cross sowing and conventional sowing methods, respectively. Paired row sowing also improved various yield associated attributes viz., number of pegs (35.1) and pod plant-1(27.6), shelling percentage (66.6) and 100-kernel weight (33.6 g), and profitability ( 19,730) in groundnut.